2022
DOI: 10.14740/jmc3866
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Severe Hemolytic Anemia and Pulmonary Embolism Secondary to Mycoplasma pneumoniae Infection

Abstract: A 27-year-old woman was admitted with a history of dry cough, breathlessness, fever, lethargy, and nausea and vomiting. On examination, she was febrile, jaundiced, and hypoxic. Blood tests revealed severe leucocytosis and severe hemolytic anemia. The chest imaging demonstrated coexisting pneumonia and pulmonary embolism. An initial blood transfusion worsened the hemolytic anemia to the point that critical care review was required. Subsequent blood tests revealed cold agglutinin hemolytic anemia due to Mycoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…While data with Legionella and CAS is sparse, correlations can be drawn from other atypical pneumonia that triggers CAS, most notably M. pneumoniae . Various case reports have demonstrated that the hemolytic process resolves with the resolution of the infection in conjunction with supportive care, as demonstrated by Eldin et al and Kanagevelu et al [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…While data with Legionella and CAS is sparse, correlations can be drawn from other atypical pneumonia that triggers CAS, most notably M. pneumoniae . Various case reports have demonstrated that the hemolytic process resolves with the resolution of the infection in conjunction with supportive care, as demonstrated by Eldin et al and Kanagevelu et al [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondary CAS due to infections are typically polyclonal and transient, resolving with the resolution of the infection, spontaneously or with antibiotics if indicated [ 7 ]. Kanagavelu et al reported a case of mycoplasma-induced CAS that resolved completely after treatment of the underlying infection [ 2 ]. Our patient responded well to doxycycline and multiple pRBC transfusions, and her 2-week follow-up after discharge showed stable Hb and no evidence of hemolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The two types are primary cold agglutinin disease (CAD) and secondary cold agglutinin syndrome (CAS), with the latter caused by underlying infections, autoimmune diseases, or malignancies [ 1 ]. Due to the potential for complications such as severe anemia and thrombosis, timely diagnosis and treatment are crucial [ 2 ]. This case report presents a challenging case of a young female with severe cAIHA, highlighting the diagnostic and therapeutic considerations for this rare and complex condition.…”
Section: Introductionmentioning
confidence: 99%